Pirfenidone in patients with progressive fibrotic interstitial lung diseases other than idiopathic pulmonary fibrosis (RELIEF): a double-blind, randomised, placebo-controlled, phase 2b trial. Issue 5 (May 2021) - Behr, Jürgen; Prasse, Antje; Kreuter, Michael; Johow, Johannes; Rabe, Klaus F; Bonella, Francesco; Bonnet, Reiner; Grohe, Christian; Held, Matthias; Wilkens, Heinrike; Hammerl, Peter; Koschel, Dirk; et al.
Summary: Background: Pirfenidone has been shown to slow disease progression in patients with idiopathic pulmonary fibrosis (IPF). However, there are few treatment options for progressive fibrotic interstitial lung diseases (ILDs)) other than IPF. In view of the pathomechanistic and clinical similarities between IPF and other progressive fibrotic ILDs, we aimed to assess the efficacy and safety of pirfenidone in patients with four non-IPF progressive fibrotic ILDs. Methods: We did a multicentre, double-blind, randomised, placebo-controlled, parallel phase 2b trial (RELIEF) in 17 centres with expertise in ILD in Germany. Eligible participants were patients aged 18–80 years with progressive fibrotic ILD due to four diagnoses: collagen or vascular diseases (ie, connective tissue disease-associated ILDs), fibrotic non-specific interstitial pneumonia, chronic hypersensitivity pneumonitis, or asbestos-induced lung fibrosis. Other eligibility criteria included a forced vital capacity (FVC) of 40–90% predicted, a diffusing capacity of the lung for carbon monoxide of 10–90% predicted, and an annual decline of FVC of at least 5% predicted despite conventional therapy, based on at least three measurements within 6–24 months before enrolment. Patients who had received any previous antifibrotic therapy were excluded. We randomly assigned patients (1:1) to either oral pirfenidone (267 mg three times per day in week 1, 534 mg three times per day in week 2, and 801 mg three times per day thereafter) or matched placebo, added to their ongoing medication. Randomisation was done centrally using permuted block randomisation with varying block sizes stratified by the four diagnostic groups. Patients, investigators, statisticians, monitors, and the study coordinator were masked to treatment assignment until database closure. The placebo-controlled study period was 48 weeks (including up-titration). The primary endpoint was absolute change in percentage of predicted FVC (FVC % predicted) from baseline to week 48 in the intention-to-treat population, with imputation of missing data by the smallest sum of squared differences and attribution of deceased patients to the lowest rank in a rank ANCOVA model. Additionally, we did linear mixed-model repeated measures slope analyses of FVC % predicted longitudinal data over the course of the study as a prespecified sensitivity analysis and post-hoc sensitivity analyses of the primary endpoint in the intention-to-treat population using imputation methods of last observation carried forward [LOCF] and a regression-based multiple imputation procedure. Safety was assessed in all patients who received at least one dose of study medication. This trial is registered with EudraCT 2014-000861-32; DRKS00009822 and is no longer recruiting. Findings: Between April 5, 2016, and Oct 4, 2018, we randomly assigned 127 patients to treatment: 64 to pirfenidone, 63 to placebo. After 127 patients had been randomised, the study was prematurely terminated on the basis of an interim analysis for futility triggered by slow recruitment. After 48 weeks and in the overall population of 127 patients, rank ANCOVA with diagnostic group included as a factor showed a significantly lower decline in FVC % predicted in the pirfenidone group compared with placebo (p=0·043); the result was similar when the model was stratified by diagnostic group (p=0·042). A significant treatment effect was also observed when applying the LOCF and multiple imputation methods to analyses of the primary endpoint. The median difference (Hodges-Lehmann estimate) between pirfenidone and placebo groups for the primary endpoint was 1·69 FVC % predicted (95% CI –0·65 to 4·03). In the linear mixed-model repeated measures slope analysis of FVC % predicted, the estimated difference between treatment and placebo groups from baseline to week 48 was 3·53 FVC % predicted (95% CI 0·21 to 6·86) with imputation of deaths as prespecified, or 2·79 FVC % predicted (95% CI 0·03 to 5·54) without imputation. One death (non-respiratory) occurred in the pirfenidone group (2%) and five deaths (three of which were respiratory) occurred in the placebo group (8%). The most frequent serious adverse events in both groups were infections and infestations (five [8%] in the pirfenidone group, ten [16%] in the placebo group); general disorders including disease worsening (two [3%] in the pirfenidone group, seven [11%] in the placebo group); and cardiac disorders (one ([2%] in the pirfenidone group, 5 [8%] in the placebo group). Adverse events (grade 3–4) of nausea (two patients on pirfenidone, two on placebo), dyspnoea (one patient on pirfenidone, one on placebo), and diarrhoea (one patient on pirfenidone) were also observed. Interpretation: In view of the premature study termination, results should be interpreted with care. Nevertheless, our data suggest that in patients with fibrotic ILDs other than IPF who deteriorate despite conventional therapy, adding pirfenidone to existing treatment might attenuate disease progression as measured by decline in FVC. Funding: German Center for Lung Research, Roche Pharma.